Study of primary hyperparathyroidism by double-phase gammagraphy using Tc99m-MIBI: preoperative detection of pathological glands - Blanco, I; Carril, J; Banzo, I; Quirce, R; Gutiérrez, C; Uriarte, I; Montero de la Peña, A; Hernández, A (Revista española de medicina nuclear, 1998)
The preoperative use of imaging techniques to localize the diseased glands in primary hyperparathyroidism is still the subject of controversy. This paper assess the use of double-phase 99mTc-MIBI scintigraphy with that purpose. We examined 37 patients with primary hyperparathyroidism before surgical intervention. Two planar images 10 minutes and 3 hours after injection of 99mTc-MIBI were acquired. Final diagnosis was adenoma in 32 patients, 30 of whom had a positive scintigraphy (sensitivity 94%), with only two false negative results. In the other five patients, four with hyperplasia and one carcinoma, scintigraphy was also positive. Radioisotopic study was of particular interest in 5 patients who had undergone previous surgery; in one case, other diseased gland was located in the neck, and an ectopic adenoma was found in the remaining four cases. Two other ectopic lesions were also MIBI positive and, in these cases, scintigraphy was a direct indication for mediastinal surgery. There was no false positive results. We conclude that the high sensitivity and easy performance make double-phase 99mTc-MIBI scintigraphy the technique of choice for the preoperative localization of diseased glands in primary hyperparathyroidism, especially in cases of adenoma. Its use is of particular interest in adenomas with aberrant location and in patients who have undergone previous surgery.